Isolated hepatic perfusion as a treatment for uveal melanoma liver metastases (the SCANDIUM trial): study protocol for a randomized controlled trial - Olofsson, Roger (BioMed Central, 2014)
BACKGROUND: Uveal melanoma is the most common primary intraocular malignancy in adults. Despite successful control of the primary tumor, metastatic disease will ultimately develop in approximately 50% of patients, with the liver being the most common site for metastases. The median survival for patients with liver metastases is between 6 and 12 months, and no treatment has in randomized trials ever been shown to prolong survival. A previous phase II trial using isolated hepatic perfusion (IHP) has suggested a 14-month increase in overall survival compared with a historic control group consisting of the longest surviving patients in Sweden during the same time period (26 versus 12 months). METHODS/DESIGN: This is the protocol for a multicenter phase III trial randomizing patients with isolated liver metastases of uveal melanoma to IHP or best alternative care (BAC). Inclusion criteria include liver metastases (verified by biopsy) and no evidence of extra-hepatic tumor manifestations by positron emission tomography–computed tomography (PET-CT). The primary endpoint is overall survival at 24 months, with secondary endpoints including response rate, progression-free survival, and quality of life. The planned sample size is 78 patients throughout five years. DISCUSSION: Patients with isolated liver metastases of uveal melanoma origin have a short expected survival and no standard treatment option exists. This is the first randomized clinical trial to evaluate IHP as a treatment option with overall survival being the primary endpoint. TRIAL REGISTRATION: ClinicalTrials.gov registration number: NCT01785316 (registered 1 February 2013). EudraCT registration number: 2013-000564-29.